Dietary patterns, breakfast consumption, meals with family and associations with common mental disorders in adolescents: a school-based cross-sectional study - Lucia Helena Almeida Gratão; Milene Cristine Pessoa; Thales Philipe Rodrigues da Silva; Luana Lara Rocha; Monique Louise Cassimiro Inácio; Tatiana Resende Prado Rangel de Oliveira; Cristiane de Freitas Cunha; Larissa Loures Mendes (BMC, 2022)
Abstract Background Adolescence is a period of transition and vulnerabilities, in which mental illnesses can develop more easily. The objective of this work is to analyze the association of dietary patterns, breakfast consumption, and the practice of having meals accompanied by the family with the presence of Common Mental Disorders in Brazilian adolescents. Methods This is a cross-sectional study which analyzed data from 71,553 Brazilian adolescents aged 12-17 years, from the Study of Cardiovascular Risk in Adolescents (Portuguese acronym, "ERICA"). Principal Component Analysis was performed to identify dietary patterns, and Logistic Regression Models were performed to identify the associations between Common Mental Disorders, dietary patterns, and eating practices that are breakfast consumption and practice of having meals accompanied by family. Results Two patterns were found, a Healthy Dietary Pattern and an Unhealthy Dietary Pattern. Adolescents classified in the second (OR: 0.79; 95% CI 0.70-0.89) or third (OR: 0.86; 95% CI 0.77-0.96) tercile of the Healthy Dietary Pattern had a lower chance of having Common Mental Disorders. Eating breakfast sometimes (OR: 0.71; 95% CI 0.61-0.83) or almost every day/every day (OR: 0.54; 95% CI 0.47-0.62), and the practice of having the main meals with the family sometimes (OR: 0.69; 95% CI 0.57-0.84) or almost every day/every day (OR: 0.50; 95% CI 0.44-0.58), decreased the chance for Common Mental Disorders. Conclusion This study observed that healthy dietary patterns are associated with better mental health in adolescents, thus should be encouraged and promoted.